2023
DOI: 10.3389/fphar.2023.1287505
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of resveratrol as chemo and radiosensitizer in cancer

Sandra Cotino-Nájera,
Luis A. Herrera,
Guadalupe Domínguez-Gómez
et al.

Abstract: One of the primary diseases that cause death worldwide is cancer. Cancer cells can be intrinsically resistant or acquire resistance to therapies and drugs used for cancer treatment through multiple mechanisms of action that favor cell survival and proliferation, becoming one of the leading causes of treatment failure against cancer. A promising strategy to overcome chemoresistance and radioresistance is the co-administration of anticancer agents and natural compounds with anticancer properties, such as the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 316 publications
0
2
0
Order By: Relevance
“…Remarkably decreased IL-1β levels in a study indicated that probiotics reduce inflammatory factor levels ( Wang et al, 2012 ). Additionally, TNF-α, a key inflammatory cytokine that regulates classical NF-κB inflammatory pathway activation, acts as both an activator and a product of NF-κB activation ( Lopetuso et al, 2013 ; Cotino-Nájera et al, 2023 ). Hence, TNF-α and NF-κB are often studied together.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably decreased IL-1β levels in a study indicated that probiotics reduce inflammatory factor levels ( Wang et al, 2012 ). Additionally, TNF-α, a key inflammatory cytokine that regulates classical NF-κB inflammatory pathway activation, acts as both an activator and a product of NF-κB activation ( Lopetuso et al, 2013 ; Cotino-Nájera et al, 2023 ). Hence, TNF-α and NF-κB are often studied together.…”
Section: Discussionmentioning
confidence: 99%
“…[ 211 ] Additionally, RES serves as a sensitizer to address the challenging issue of chemotherapy resistance. [ 212 , 213 ] For instance, RES enhances the sensitivity of GBM to temozolomide by downregulating STAT3 and O6‐methylguanine‐DNA methyltransferase (MGMT) levels associated with alkylating agent resistance, effectively attenuating tumor growth. [ 214 ] RES can also increase the chemosensitivity of GBM cells to doxorubicin by inhibiting the PI3K/AKT and P‐glycoprotein pathways.…”
Section: Tcm For Cns Diseasesmentioning
confidence: 99%